SELF ABILITY, COMPENSATION AND SELF-EFFICIENCY ON EMPLOYEE PERFORMANCE AT SEMEN PADANG HOSPITAL - Nila Pratiwi; Farhana Widia (Jurnal Ipteks Terapan, 2023)
Employee performance at Semen Padang Hospital. The population in this study were all employees of Semen Padang Hospital. The sample selection technique used porpusive sampling and obtained a sample of 72 samples. The method of analysis using multiple linear regression analysis with SPSS 21.0. Based on the results of research and hypothesis testing that have been carried out, the results of the study can be said that Independent Ability has a significant effect on employee performance at Semen Padang Hospital. Compensation has a positive and significant effect on employee performance at Semen Padang Hospital. Self Efficacy has no significant effect on employee performance at Semen Padang Hospital. Self ability, compensation, and self efficacy together have a positive and significant effect on employee performance at Semen Padang Hospital. And the contribution of the independent variables Self ability (X1), Compensation (X2) and Self Efficacy (X3) to the dependent employee performance (Y) is 0.792 or 79,2%. While the remaining 0.208 or 20,8% is influenced by other variables outside the study. It is expected to always improve self-ability and compensation in the company, because self-ability and compensation can improve employee performance. Companies are also advised to increase Self Efficacy through increasing indicators related to Self Efficacy, because Self Efficacy has not been able to provide a significant influence on employee performance.